1995
DOI: 10.1074/jbc.270.40.23345
|View full text |Cite
|
Sign up to set email alerts
|

Self-potentiation of Ligand-Toxin Conjugates Containing Ricin A Chain Fused with Viral Structures

Abstract: A chimeric protein was obtained by fusing together the ricin toxin A chain (RTA) gene and a DNA fragment encoding the N terminus of protein G of the vesicular stomatitis virus. Chimeric RTA (cRTA) retained full enzymic activity in a cell-free assay, but was 10-fold less toxic against human leukemic cells than either native RTA (nRTA) or unmodified recombinant RTA (rRTA). However, conjugates made with cRTA and human transferrin (Tfn) showed 10 -20-fold greater cell killing efficacy than Tfn-nRTA or Tfn-rRTA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…To clone the 3 chimeric dianthins (KFT25DIA, pHA2DIA and pJVEDIA), the 5Ј end of the gene was modified by PCR to insert a SoI restriction site just downstream of NcoI. The SoI site and the upstream site NcoI were used to ligate in 5Ј with respect to the toxin gene one of 3 double stranded oligonucleotides coding for: (i) the peptide pHA2 (sequence GLFEAIAGFIENGWEGMID, from the N terminus of the influenza virus hemagglutinin) (Wagner et al, 1992), (ii) the peptide pJVE (sequence GLFEALLELLE-SLWELLLEA, designed upon known properties of membraneacting peptides) (Pécheur et al, 1999), or (iii) the peptide KFT25 (sequence KFTIVFPHNQKGNWKNVPSNYHYCP, from the Nterminus of vesicular stomatitis virus protein G) (Chignola et al, 1995). The 3 new plasmids were designated pET11d-pHA2DIA, pET11d-pJVEDIA and pET11d-KFT25DIA respectively.…”
Section: Cloning Of Chimeric Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…To clone the 3 chimeric dianthins (KFT25DIA, pHA2DIA and pJVEDIA), the 5Ј end of the gene was modified by PCR to insert a SoI restriction site just downstream of NcoI. The SoI site and the upstream site NcoI were used to ligate in 5Ј with respect to the toxin gene one of 3 double stranded oligonucleotides coding for: (i) the peptide pHA2 (sequence GLFEAIAGFIENGWEGMID, from the N terminus of the influenza virus hemagglutinin) (Wagner et al, 1992), (ii) the peptide pJVE (sequence GLFEALLELLE-SLWELLLEA, designed upon known properties of membraneacting peptides) (Pécheur et al, 1999), or (iii) the peptide KFT25 (sequence KFTIVFPHNQKGNWKNVPSNYHYCP, from the Nterminus of vesicular stomatitis virus protein G) (Chignola et al, 1995). The 3 new plasmids were designated pET11d-pHA2DIA, pET11d-pJVEDIA and pET11d-KFT25DIA respectively.…”
Section: Cloning Of Chimeric Toxinsmentioning
confidence: 99%
“…Moreover, ITs are essentially hydrophilic, therefore cell entry is a somewhat low-efficiency process in general, and especially in the case of ITs made with RTA or RIP-I toxins. We have shown (Chignola et al, 1995) that genetic grafting of a "membraneacting" peptide (KFT25) (Schlegel and Wade, 1984) onto RTA increased the cytotoxicity of transferrin-bound RTA, while reducing the intrinsic toxicity of unbound chimeric toxin for cells in vitro. We have here genetically linked 3 different membraneacting peptides to wild-type dianthin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus HA-2 peptide can be used to enhance the cytotoxicity of ITs by facilitating their entry into target cells. Chignola et al (1995) modified RTA by fusing it to a protein structure derived from viral envelope, thus conferring the cytosoltargeting properties of the virus onto the cytotoxic enzyme-modified RTA. A peptide representing the primary sequence of the 25 N-terminal amino acid of protein G of the vesicular stomatitis virus envelope (KFT25) was found to have pH-dependent membrane-destabilizing properties.…”
Section: Viruses and Viral Particlesmentioning
confidence: 99%
“…However, immunospecificity was seriously reduced for the peptide modified targeted toxins, which were equally cytotoxic for target antigen negative cell lines (Flavell, unpublished data). Similarly, Chignola and coworkers [69] genetically fused a 19 amino acid peptide derived from the N-terminus of HA2 to ricin A chain (RTA) coupled to transferrin, but this failed to increase the cytotoxicity of this chimeric targeted toxin molecule for human transferrin receptor expressing cell lines. In contrast the same workers showed that KFT25, a 25 amino acid peptide derived from the N-terminal end of the fusogenic G protein from vesicular stomatitis virus when fused to RTA in turn conjugated to transferrin showed an almost four-fold increase in toxicity for the same cell lines over the unmodified targeted toxin transferrin-RTA.…”
Section: Figurementioning
confidence: 99%